Spatiality and Symbolic Expression: On the Links between Place and Culture - Stefanova Radoulska, Svetlana (Transnational Literature, 2017)
Reseña de "Spatiality and Symbolic Expression: On the Links between Place and Culture" de Bill Richardson, por Svetlana Stefanova. Palgrave Macmillan, 2015.
A growing number of studies acknowledge the interpretative potential of spatial models for the understanding of diverse cultural phenomena. Published as part of Geocriticism and Spatial Literary Studies, a book series edited by Robert T. Tally Jr., the volume reflects the increasing global interest in spatiality and the immense expanse of spatial approach within the humanities. According to its editor, Bill Richardson, the volume examines ‘how spatial realities inform symbolic expression and how a variety of forms of symbolic expression and cultural production rely on those spatial realities to achieve their ends’ (2). The essays seek to extend recent developments in the field of spatio-cultural studies and apply new conceptual approaches to a variety of cultural forms.
Keywords: reseña; libros; Emerging